Iron‐Catalyzed, Atom‐Economical, Chemo‐ and Regioselective Alkene Hydroboration with Pinacolborane1. Issue 13 (18th February 2013) - Zhang, Lei; Peng, Dongjie; Leng, Xuebing; Huang, Zheng
<x xml:space="preserve">Abstract</x> Precious iron: A new PNN iron complex has been developed for use in an iron‐catalyzed alkene hydroboration reaction under mild conditions. The environmentally friendly and earth‐abundant iron catalyst system is superior to precious‐metal systems in terms of efficiency and selectivity for α‐olefin hydroborations with pinacolborane.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>